2004
DOI: 10.1021/jm0493156
|View full text |Cite
|
Sign up to set email alerts
|

(2R)-4-Oxo-4-[3-(Trifluoromethyl)-5,6-dihydro[1,2,4]triazolo[4,3-a]pyrazin- 7(8H)-yl]-1-(2,4,5-trifluorophenyl)butan-2-amine:  A Potent, Orally Active Dipeptidyl Peptidase IV Inhibitor for the Treatment of Type 2 Diabetes

Abstract: A novel series of beta-amino amides incorporating fused heterocycles, i.e., triazolopiperazines, were synthesized and evaluated as inhibitors of dipeptidyl peptidase IV (DPP-IV) for the treatment of type 2 diabetes. (2R)-4-Oxo-4-[3-(trifluoromethyl)-5,6-dihydro[1,2,4]triazolo[4,3-a]pyrazin-7(8H)-yl]-1-(2,4,5-trifluorophenyl)butan-2-amine (1) is a potent, orally active DPP-IV inhibitor (IC(50) = 18 nM) with excellent selectivity over other proline-selective peptidases, oral bioavailability in preclinical specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
493
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 792 publications
(513 citation statements)
references
References 37 publications
14
493
0
3
Order By: Relevance
“…In an animal experiment, LC15-0444 shows inhibition of DPPIV activity by Z80%, which is associated with a maximal short-term lowering of glucose levels. 22 In addition, a twofold augmentation of postprandial active GLP-1 levels is associated with similar effects. 22 A phase I study conducted in healthy Korean male subjects after single administration of LC15-0444 at doses of either 25, 50, 100, 200, 400, or 600 mg found that a single dose of LC15-0444 exhibited linear PK properties over the range of 50-400 mg in study subjects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In an animal experiment, LC15-0444 shows inhibition of DPPIV activity by Z80%, which is associated with a maximal short-term lowering of glucose levels. 22 In addition, a twofold augmentation of postprandial active GLP-1 levels is associated with similar effects. 22 A phase I study conducted in healthy Korean male subjects after single administration of LC15-0444 at doses of either 25, 50, 100, 200, 400, or 600 mg found that a single dose of LC15-0444 exhibited linear PK properties over the range of 50-400 mg in study subjects.…”
Section: Discussionmentioning
confidence: 97%
“…22 In addition, a twofold augmentation of postprandial active GLP-1 levels is associated with similar effects. 22 A phase I study conducted in healthy Korean male subjects after single administration of LC15-0444 at doses of either 25, 50, 100, 200, 400, or 600 mg found that a single dose of LC15-0444 exhibited linear PK properties over the range of 50-400 mg in study subjects. 23 In addition, PK characteristics were not significantly influenced by food, and doses Z200 mg of LC15-0444 inhibited plasma DPP IV activity by 480% over a 24-h dosing interval, and a 600 mg dose increased active GLP-1 levels after a standardized meal.…”
Section: Discussionmentioning
confidence: 97%
“…,5-trifluorophenyl)butan-2-amine is a powerful, vocally active (DPP-IV) inhibitor with excellent selectivity above the other prolineselective peptidases [16].…”
Section: β-Amino Amidesmentioning
confidence: 99%
“…1 The incretin hormone glucagon-like peptide 1 (GLP-1) has been the subject of intense research efforts related to the treatment of type 2 diabetes. 2 Secreted from the L cells of the small intestine, 3 GLP-1 stimulates glucose-induced insulin secretion, inhibits glucagon secretion, 4 and delays the gastric emptying, all of which are beneficial in controlling the blood glucose. 5 GLP-1 is one of the substrates of dipeptidyl peptidase-4 (DPP-4, also known as CD26).…”
mentioning
confidence: 99%